Izgubljeni grob - Kavur, Boris (Annales. Series historia et sociologia, 2008)
During an archaeological survey of the Leclerc shopping centre construction site in Maribor a collection of bronye ribbed bracelets was uncovered, which can be interpreted as an alleged older Iron Age female grave. Traces that would point to the existence of a burial mound were not discovered, therefore, we can assume that these were destroyed due to the intensive agricultural activity in the last period. Recently, completely destroyed burial mounds were also discovered elsewhere in the lowlands of the Pohorje foothills, which would suggest that the landscape was strongly changed with intensive agricultural use. Despite all, the location of the alleged burial is surprising, as it is far from any other burial mound cemeteries, as well as the central Iron Age settlement in Poštela. Graves with similar grave goods were uncovered in burial mound 38 at Lepa ravna and Razvanje, as well as on the burial mound cemeteries in Kleinklein and at Breg. In all cases, these are wealthier female graves, bearing witness to the important social status of the deceased due to their position and grave inventories. The structures and techniques of building grave chambers in the examples mentioned were different, regarding whether the deceased was buried in together with a notable man or alone. A wider geographical and chronological comparison shows that the numerous ribbed bracelets in these graves represent supra-regional fashion elements in female burials of the late HaC and early HaD; the manner of burial, where the grave goods were incinerated together with the deceased and perhaps even destroyed prior to the cremation, points to an integration in a longevous local tradition.
Keywords: archaeology; arheologija; arheološke najdbe; grobovi; Koroška; nakit; starejša železna doba; Styria; Štajerska